2018
DOI: 10.4049/jimmunol.1700553
|View full text |Cite
|
Sign up to set email alerts
|

ILT3.Fc–CD166 Interaction Induces Inactivation of p70 S6 Kinase and Inhibits Tumor Cell Growth

Abstract: The blockade of immune checkpoints by anti-receptor and/or anti-ligand mAb is one of the most promising approaches to cancer immunotherapy. The interaction between Ig-like transcript 3 (ILT3), a marker of tolerogenic dendritic cells, also known as LILRB4/LIR5/CD85k, and its still unidentified ligand on the surface of activated human T cells is potentially important for immune checkpoint blockade. To identify the ILT3 ligand, we generated mAb by immunizing mice with Jurkat acute T cell leukemia, which binds ILT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 53 publications
(67 reference statements)
1
37
1
Order By: Relevance
“…Similar to shCD6, chimeric soluble ILT3 (ILT3.Fc) inhibited in vitro T cell proliferation and differentiation to Treg, and also tumor cell growth and migration in an ALCAM-dependent manner cells. 27 These observations support the targeting of ALCAM for immunotherapeutic purposes in cancer. On this basis, we tested the efficacy of sustained smCD6 delivery by means of AAV-based gene transfer-a successful strategy in several preclinical models and in recent clinical cancer trials.…”
Section: Flow Cytometry Analysessupporting
confidence: 52%
See 2 more Smart Citations
“…Similar to shCD6, chimeric soluble ILT3 (ILT3.Fc) inhibited in vitro T cell proliferation and differentiation to Treg, and also tumor cell growth and migration in an ALCAM-dependent manner cells. 27 These observations support the targeting of ALCAM for immunotherapeutic purposes in cancer. On this basis, we tested the efficacy of sustained smCD6 delivery by means of AAV-based gene transfer-a successful strategy in several preclinical models and in recent clinical cancer trials.…”
Section: Flow Cytometry Analysessupporting
confidence: 52%
“…in vitro tumor cell growth and migration assays Tumor cell proliferation was monitored as reported elsewhere. 27 Wound healing technique was used to assess tumor cell migration. 28 on October 12, 2020 by guest.…”
Section: Flow Cytometry Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-LILRB4 antibodies reactivate T cells and blocked development of monocytic leukemia. 77 Although it was demonstrated that ApoE binding can activate LILRB4, 77 and LILRB4 interaction with CD166 mediates its inhibitory effect on tumor cells, 85 further investigations are needed to clarify whether LILRB4 on monocytic cells can directly bind and act on a surface protein (ideally an immune inhibitory receptor) on T cells.…”
Section: Mhc I-lilrb1mentioning
confidence: 99%
“…It is capable of mediating both CD166-CD166 homophilic interactions as well as heterophilic interactions with CD6 (Degen, van Kempen et al 1998). Recently, CD85k has been identified as a ligand which binds to CD166 and in turn blocks tumor growth in CD166+ tumor cell lines (Xu, Chang et al 2018). In hematopoiesis, CD166 is an important functional marker of HSC and is critical for the competence of the niche , Chitteti, Cheng et al 2013, Chitteti, Kobayashi et al 2014.…”
Section: Discussionmentioning
confidence: 99%